2001
DOI: 10.1046/j.1440-172x.2001.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' beliefs about the conditions that hinder or support evidence‐based nursing

Abstract: The aim of this study was to identify the conditions that Australian nurses believe support or hinder the development of evidence-based nursing. A survey instrument was developed from the results of content analysis of the UK and the USA research and of interviews with 12 Australian nurses. Eight hundred and sixteen nurses working in three large hospitals responded representing a response rate of 65%. Principal axis factor analysis of the survey results revealed six conditions that the participants believed we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 10 publications
5
93
0
12
Order By: Relevance
“…However, this stands in contrast to the numbers of respondents regularly using such databases, and those who felt that their practice would improve if they had greater access to research literature. Availability of access does not necessarily mean convenience and ease of access, and the lack of time required to implement evidence-based practice that we found and that has been reported in numerous previous studies across different professional groups (Tomlin, 1999;Humphris et al, 2000;Curtin and Jaramazovic, 2001;Nagy et al, 2001) could be considered as a significant factor for access. Our results suggest that mere availability of computers may not be enough to enable practitioners to regularly and confidently engage in evidence-based practice.…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 51%
See 2 more Smart Citations
“…However, this stands in contrast to the numbers of respondents regularly using such databases, and those who felt that their practice would improve if they had greater access to research literature. Availability of access does not necessarily mean convenience and ease of access, and the lack of time required to implement evidence-based practice that we found and that has been reported in numerous previous studies across different professional groups (Tomlin, 1999;Humphris et al, 2000;Curtin and Jaramazovic, 2001;Nagy et al, 2001) could be considered as a significant factor for access. Our results suggest that mere availability of computers may not be enough to enable practitioners to regularly and confidently engage in evidence-based practice.…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 51%
“…Lack of time is perceived by therapists, general practitioners and nurses to be the major barrier to implementing evidence-based practice (Tomlin, 1999;Humphris et al, 2000;Curtin and Jaramazovic, 2001;Nagy et al, 2001;Vallino-Napoli and Reilly, 2004;McKenna et al, 2005;Zipoli and Kennedy, 2005). Nagy et al (2001) report that nurses expressed a lack of confidence in the willingness of their organisation to support evidence-based practice. The combination of this lack of confidence and the perceived time constraints could be related to the fact that some professionals, e.g.…”
Section: Background and Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Interaction should take place between the organization's direct care providers and management such as nurse managers, to support these changes (Retsas, 2000;Nagy et al, 2001;Berwick, 2003;LoBiondo-Wood and Haber, 2006). As social and organizational factors interfere with the application of research findings, they need to be identified and addressed prior to the development of evidence-based practice or application of an evidence-based practice initiative to other practice areas within the organisation.…”
Section: Process Of Introducing Evidence-based Practicementioning
confidence: 99%
“…Un hándicap encontrado en esta escala es que se desarrolló en el ámbito sanitario Australiano, por lo tanto, la conclusión abordaba únicamente la mejora de la enfermería basada en la evidencia en Australia 75 .…”
unclassified